Comparison of marine and terrestrial ecosystems: suggestions of an evolutionary perspective influenced by environmental variation. (5th November 2018) - Steele, John H; Brink, Kenneth H; Scott, Beth E
Abstract: The transition of plants and animals from sea to land required adaptation to a very different physical and chemical environment. In this paper, we focus on the consequences of the differences between the magnitude of the variability of ocean and atmospheric dynamics, with the ocean environment (in particular temperature and currents) being two to three orders of magnitude less variable than that on land. We suggest that greater insights on possible responses of marine vs. terrestrial systems to rapid climate change can be gained by considering that terrestrial vertebrates, invertebrates and plants have evolved from marine organisms that, pre-Cambrian, had early life history developmental stages as planktonic larvae. Marine larvae were/are adapted to the predictable and minimal range of temperature changes and regularities in ocean currents, as most organisms utilize the energy in these currents as an "auxiliary" source for predictable gamete and larvae dispersal. Post-Cambrian, on land, no such simple strategy was available; instead, most terrestrial organisms have evolved reproductive strategies and behaviours to eliminate, or at least minimize, the consequences of much larger atmospheric variability. Adapting our future use of these systems sensibly will require greater understanding of how the two regimes respond to rapid climate change.